1995
DOI: 10.1080/01688639508405120
|View full text |Cite
|
Sign up to set email alerts
|

Spatial attention in the mental architecture: Evidence from neuropsychology

Abstract: Using neuropsychological evidence, this paper examines whether spatial attention functions as a domain-specific module or as a more general-purpose central processor. Data are presented from two spatial attention cuing tasks completed by subjects, with an acquired attentional deficit, and control subjects. In both tasks, an arrow indicated with high probability the side of response (response task) or the side of space on which the stimulus would appear (visuospatial task). In the response task, the stimuli app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…These data may imply that there are multiple frames of reference in which neglect arises, and that the variety of lesion sites or severities will influence these multiple frames in different ways. Similar observations regarding the effect of severity on performance have been made by Behrmann, Black, and Murji (1995) and by Driver and Halligan (1991). This participant variability may be used to great advantage in future research.…”
Section: Discussionsupporting
confidence: 53%
“…These data may imply that there are multiple frames of reference in which neglect arises, and that the variety of lesion sites or severities will influence these multiple frames in different ways. Similar observations regarding the effect of severity on performance have been made by Behrmann, Black, and Murji (1995) and by Driver and Halligan (1991). This participant variability may be used to great advantage in future research.…”
Section: Discussionsupporting
confidence: 53%
“…This, however, introduced a potential problem in the interpretation of the results. Patients with left neglect may show a response bias when asked to press lateralized keys (even if they are close to each other, as in the present study), with faster responses for right-sided keys than for left-sided keys (Behrmann, Black, & Murji, 1995;Làdavas, Farne, Carletti, & Zeloni, 1994). Thus, slower RTs for left-sided imagined locations might in fact originate from a response bias, and not from an imaginal impairment 1 .…”
Section: Introductionmentioning
confidence: 62%
“…Some stimuli are preferentially processed because the brain presumably has been designed to process salient stimuli more so than nonsalient stimuli. Experimental studies have generally confirmed that relevant or salient visual stimuli produce deeper or more effective cognitive processing than other irrelevant stimuli (Behrmann, Black, & Murji, 1995;Danckert et al, 2000;Egeth & Yantis, 1997;Fuster, 1990;Yantis & Jonides, 1984). Emotional stimuli, in particular, have been shown to naturally engage the visual attention system (Keil, Moratti, Sabatinelli, Bradley, & Lang, 2005).…”
Section: Attention and Emotionmentioning
confidence: 95%